2020
DOI: 10.1186/s12944-020-01349-w
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol intake during pregnancy and lactation re-programs adiposity and ameliorates leptin resistance in male progeny induced by maternal high-fat/high sucrose plus postnatal high-fat/high sucrose diets via fat metabolism regulation

Abstract: Background: Maternal obesity is an emerging problem in the modern world. Growing evidence suggests that intrauterine high-fat (HF) exposure may predispose progeny to subsequent metabolic challenges. Progeny born to mothers who ate an HF diet also tends to eat an HF diet when growing and aggravate metabolic issues. Thus, the generational transmission of obesity is cyclical. Developing a strategy to prevent the occurrence of metabolic syndrome related to prenatal and/or postnatal HF diet is important. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Different early life insults, such as maternal gestational diabetes (MGD), obesity and nutritional imbalances, have been used to study the potential protective effects of resveratrol. As summarized in Table 1 , the most commonly used experimental models for these studies involve rodents [ 13 , 29 , 30 , 31 , 61 , 65 , 66 , 67 , 68 , 69 ]. However, in an attempt to approximate human physiology, some studies have also been performed in nonhuman primates [ 62 , 63 , 64 ].…”
Section: Effects Of Resveratrolmentioning
confidence: 99%
See 3 more Smart Citations
“…Different early life insults, such as maternal gestational diabetes (MGD), obesity and nutritional imbalances, have been used to study the potential protective effects of resveratrol. As summarized in Table 1 , the most commonly used experimental models for these studies involve rodents [ 13 , 29 , 30 , 31 , 61 , 65 , 66 , 67 , 68 , 69 ]. However, in an attempt to approximate human physiology, some studies have also been performed in nonhuman primates [ 62 , 63 , 64 ].…”
Section: Effects Of Resveratrolmentioning
confidence: 99%
“…We used a Wistar rat model where dams received a low-fat diet (LFD; 10.2% Kcal from fat) or HFD (61.6% Kcal from fat) during gestation and lactation to determine the effect of maternal resveratrol intake (2–2.5 mg/kg/day in drinking water) during pregnancy and lactation on the metabolism of the offspring at weaning and observed that these effects depend on the type of diet ingested by the mother and the offspring’s sex [ 30 ]. Of note, we used a low dose of resveratrol that can be easily ingested in a normal diet and based on its described hormetic property [ 24 , 69 ]. We found that resveratrol decreased body weight (BW) and adipose tissue (visceral and subcutaneous) mass at weaning in offspring from HFD-fed dams but had no effect on these parameters in the offspring from LFD-fed dams.…”
Section: Effects Of Resveratrolmentioning
confidence: 99%
See 2 more Smart Citations
“…[86] assessed the effect of maternal resveratrol intake of obese rats and found that resveratrol treatment restored adiponectin, AKT phosphorylation, brain-derived neurotrophic factor (BDNF) in male fetal brain; increased blood pressure, reduced increased body weight, peripheral insulin resistance in adult male offspring, further demonstrating that the intervention with this polyphenol may protects offspring against HFD-induced obesity. Another study using HFD-obese rats model [87] highlighted that the maternal resveratrol supplementation has a reprogramming role for progeny through lipid metabolic modulation. The authors showed that resveratrol treatment decreased lipogenesis and SIRT1 protein expression, attenuated leptin resistance, and increased lipolysis for progeny, resulting in an anti-obesity effect.…”
Section: Polyphenols Effect On Obesity and Maternal Programmingmentioning
confidence: 99%